2016
DOI: 10.1152/ajpregu.00450.2015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bladder and external urethral activity in mice with or without spinal cord injury—a comparison study with rats

Abstract: To clarify the lower urinary tract function in mice, we compared bladder and urethral activity between rats and mice with or without spinal cord injury (SCI). Female Sprague-Dawley rats and C57BL/6N mice were divided into five groups:1) spinal intact (SI) rats,2) SI mice,3) pudendal nerve transection (PNT) SI mice,4) spinal cord injury (SCI) rats, and 5) SCI mice. Continuous cystometry (CMG) and external urethral sphincter (EUS)-electromyogram (EMG) analyses were conducted under an awake, restrained condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 64 publications
(136 citation statements)
references
References 20 publications
7
128
1
Order By: Relevance
“…Thus, it is possible that the contribution of A-fiber bladder afferents to SCI-induced lower urinary tract (LUT) dysfunction might be different between mice and rats. In this regard, we recently reported that the behavior of EUS during the voiding reflex, which is still dependent on capsaicin-insensitive A-fiber afferents after SCI (Cheng and de Groat, 2004), is quite different in rats and mice (Kadekawa et al, 2016) although C-fiber dependent NDO during urine storage is similarly observed between these two species after SCI (McCarthy et al, 2009; Wada et al, 2017). In SCI rats, EUS bursting occurs during voiding bladder contractions, which coincides with small-amplitude IVP oscillations during cystometry.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, it is possible that the contribution of A-fiber bladder afferents to SCI-induced lower urinary tract (LUT) dysfunction might be different between mice and rats. In this regard, we recently reported that the behavior of EUS during the voiding reflex, which is still dependent on capsaicin-insensitive A-fiber afferents after SCI (Cheng and de Groat, 2004), is quite different in rats and mice (Kadekawa et al, 2016) although C-fiber dependent NDO during urine storage is similarly observed between these two species after SCI (McCarthy et al, 2009; Wada et al, 2017). In SCI rats, EUS bursting occurs during voiding bladder contractions, which coincides with small-amplitude IVP oscillations during cystometry.…”
Section: Discussionmentioning
confidence: 99%
“…In SCI rats, EUS bursting occurs during voiding bladder contractions, which coincides with small-amplitude IVP oscillations during cystometry. Furthermore, α-bungarotoxin, a neuromuscular blocking agent, reduces voiding by suppressing EUS bursting activity, which is also necessary for efficient urine elimination in normal rats (Yoshiyama et al, 2000), indicating that EUS bursting activity recovers after SCI in rats and is able to induce relatively efficient voiding (Kadekawa et al, 2016). However, SCI mice do not exhibit clear EUS bursting or IVP oscillations during voiding, but rather exhibit periods of reduced EUS activity during voiding accompanied by a slowly developing large-amplitude reduction in IVP (Kadekawa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations